Regional gene therapy for bone healing using a 3D printed scaffold in a rat femoral defect model. Issue 11 (21st May 2021) - Kang, H Paco; Ihn, Hansel; Robertson, Djani M; Chen, Xiao; Sugiyama, Osamu; Tang, Amy; Hollis, Roger; Skorka, Tautis; Longjohn, Donald; Oakes, Daniel; Shah, Ramille; Kohn, Donald; et al.
Abstract: At the present time there are no consistently satisfactory treatment options for some challenging bone loss scenarios. We have previously reported on the properties of a novel 3D‐printed hydroxyapatite‐composite material in a pilot study, which demonstrated osteoconductive properties but was not tested in a rigorous, clinically relevant model. We therefore utilized a rat critical‐sized femoral defect model with a scaffold designed to match the dimensions of the bone defect. The scaffolds were implanted in the bone defect after being loaded with cultured rat bone marrow cells (rBMC) transduced with a lentiviral vector carrying the cDNA for BMP‐2. This experimental group was compared against 3 negative and positive control groups. The experimental group and positive control group loaded with rhBMP‐2 demonstrated statistically equivalent radiographic and histologic healing of the defect site (p > 0.9), and significantly superior to all three negative control groups (p < 0.01). However, the healed defects remained biomechanically inferior to the unoperated, contralateral femurs (p < 0.01). When combined with osteoinductive signals, the scaffolds facilitate new bone formation in the defect. However, the scaffold alone was not sufficient to promote adequate healing, suggesting that it is not substantially osteoinductive as currently structured. The combination of gene therapy with 3D‐printed scaffolds is quite promising, but additional work is required to optimize scaffold geometry, cell dosage and delivery.